Communication Strategy for Handling Cases of Stunting and Bad Nutrition Through The 2023 Stunting Free Program (Bessan) in Cipocok District, Serang City - Azhar Firdausi, Indrianti; Aries, Aries (Indonesian Journal of Social Science Research, 2024)
Cases of stunting and malnutrition that children suffer from or have the potential to have negative consequences for the future of the younger generation. There are 91 cases in Cipocok Jaya District spread across 8 villages. This occurs due to various factors including poverty, low education, lack of knowledge regarding good nutritional intake for children. A strategy is needed to communicate intensively with communities with stunted and malnourished children so that they can get out of this situation. This research uses a qualitative approach through observation and interview data collection. The research results show that the communication strategy in handling stunting and malnutrition through the Stunting Free 2023 (Bessan) program in Cipocok Jaya District, Serang City uses a communication strategy approach which includes getting to know the audience, compiling messages, determining methods and selection and use of media which has been effective. The communication strategy to get to know the audience is carried out through surveys and data collection, identifying indicators of sufferers and potential stunting. The second strategy determines the micro-scale goal of reducing stunting sufferers, the macro-scale of stunting cases at zero, where this treatment accommodates community self-help. The next communication strategy is to develop messages so that people's lifestyle behavior becomes healthy by conveying the importance of nutritious food intake for children. Methods for determining the methods used are socialization and counseling, accommodating community self-help through healthy exercise activities, regular recitations, and Gowes Lur events. This series of activities is a collaborative innovation in Cipocok Jaya District which involves stackholders starting from the Serang City Health Office, Serang City DP3AKB, KUA, as well as cadres from both posyandu cadres and PKK Community Institution cadres. Research findings show the importance of consistent mentoring or accompanying posyandu cadres and PKK community organizations as an important instrument for a sustainable communication strategy in efforts to reduce stunting and malnutrition rates.